Exploring Mentoring Skills to Assist New Nurses: Mentors’ and Mentees’ Perspectives - Sok Fong, Tie (Human Resource Management Academic Research Society, 2021)
Studies on Western context have reported on the mentor skills needed such as the role of interpersonal comfort in mentoring relationships as well as the role of age in mentoring relationships. There are limited studies in exploring the effectiveness on the most relevant skills needed by mentors in assisting the new nurses toward becoming an effective healthcare provider in the Malaysian public hospital context. The mentors’ roles can be summarized into the general and specific role on the basis of the goal and the purpose of the mentoring. Mentor roles can be very broad and almost include everything under the sky of learning contract, therefore, the need to be more specific and clear direction in order to have clear understanding between the mentor, mentee and the organization. Data were collected from four pairs of mentors and mentees (eight informants) working in a public hospital in Sarawak, Malaysia, using openended questionnaires and analysed using content analysis. Findings revealed that the required skills of the mentors to better assist new nurses at the workplace can be captured through the acronym S.K.I.L.L.S. Hence, the nurses’ -management training and development programme related to S.K.I.L.L. acronym is relevant to be conducted among the new nurses. This strategy suggested because too many and unspecified roles may bring negative experiences for both mentor and mentee which may result in dysfunctional mentoring